ISLAM, MEDIA SOSIAL DAN MILENIAL: Penggunaan Grup Whatsapp Sebagai Media Komunikasi Remaja Islam Wonorejo Malang - Muhammad Hamdan Yuwafik (Civiliza Publishing, 2020)
This paper tries to illustrate how to use the WhatsApp group as a communication medium for the Riswo Village Druju Sumbermanjing Wetan Malang. It is a descriptive qualitative research using the approach of organizational communication theory. The results of this research are organizational communication carried out by Riswo Village management of Druju Sumbermanjing Wetan Malang in accordance with organizational communication functions including, informative, regulative, persuasive and integrative functions. The target audience of the Drwo Village Riswo administrators in this study were all the Drwo Village Riswo administrators who had been recruited and became part of the Riswomprogram Riswomilik Pesuju management group of Druju Village. There are three uses of the WhatsApp group as an organizational communication medium. First, it is more efficient in terms of time, space and resources. Second, it facilitates participation, understanding and reception of messages, and third, satisfaction in the use of WhatsApp groups.